Caraterização por Microssonda Eletrônica dos Teores de Cloro de Apatitas e sua Importância nos Estudos de Traços de Fissão - MALLMANN, GUILHERME; CUPERTINO, JOSÉ ANTÔNIO; CHEMALE JR, FARID (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> Apatite Fission Track Analysis (AFTA) provides important information for geochronology and is used in different tectonic settings. For example, in the study of sedimentary basins it helps estimate subsidence rates and dates periods of uplift of source areas and tectonic pulses. In geomorphology AFTA also helps to quantify rates of erosion and long-term continental denudation. The chlorine contents in apatites influences the ages obtained from fission track dating. Commonly, apatites with more than 0,4 wt% chlorine yield older ages than fluorapatites (Laslett, et al., 1987), because the stability of the tracks changes as chlorine content increases and consequently chlorine rich-apatites are more resistant to the temperature changes than fluorapatites (Green, 1992). We investigated this problem by first determining the chlorine contents of apatites with the microprobe before apatite fission track dating. We studied four samples of the sandstones from the Reconcavo and Camamu Basins using a total of 198 spots in different apatites. We calibrated CAMECA SX50 electron microprobe using 30 spots from the crystal fragment Durando apatite standard, which has a mean chlorine value of 0,42 wt%. The comparison of the chlorine contents of the apatites of these basins with the ages obtained by AFTA indicates some changes in the individual grains in two samples. These changes are related with the current chlorine content in the apatites, once the individual ages are sometimes distributed as straight line, whose inclination is function of the chlorine content. In the other hand, two samples with modest chlorine content there was not this linear correlation.